(untitled) (Global Journal of Management and Business Research, 2023)
Tourism is the third most crucial socio-economic sector that generates income and employment in the Republic of Benin where it occupies a prominent place in the country s development policies In response to the sustainable development requirements tourists are worldwide more and more demanding on the quality and diversity of the services they receive As such strengthening the tourism sector requires environmentally and socio-economically sustainable innovations Bees with their great ecological and socio-economic functions offer many facets which can be valued to support the well-diversified tourism heritage of the Republic of Benin This review analyses existing tourism heritage the diversity of bees and apicultural practices in the country and their susceptibility to apitourism development Tourism promotion strategies based on the products and the ecological services of social and solitary bee species were analysed per suggested ecotourism region of the country The involved actors their roles and responsibilities as well as the challenges that may emerge from integrating the bee sector into the tourism heritage of the country were also analysed